Review on spectral decomposition of Hooke’s tensor for all symmetry groups of linear elastic material - KOWALCZYK-GAJEWSKA, Katarzyna; OSTROWSKA-MACIEJEWSKA, Janina (Engineering Transactions, 2009)
The spectral decomposition of elasticity tensor for all symmetry groups of a linearly elastic material is reviewed. In the paper it has been derived in non-standard way by imposing the symmetry conditions upon the orthogonal projectors instead of the stiffness tensor itself. The numbers of independent Kelvin moduli and stiffness distributors are provided. The corresponding representation of the elasticity tensor is specified.